Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1186/s12918-015-0145-3
|View full text |Cite
|
Sign up to set email alerts
|

microRNAs’ differential regulations mediate the progress of Human Papillomavirus (HPV)-induced Cervical Intraepithelial Neoplasia (CIN)

Abstract: BackgroundmicroRNA (miRNA)’s direct regulation on target mRNA is affected by complex factors beyond miRNA. Therefore, at different stages during the course of carcinogenesis, miRNA may regulate different targets, which we termed ‘miRNA’s differential regulation’. HPV-induced cervical intraepithelial neoplasia (CIN) is an important pre-cancerous course ahead of cervical cancer formation. Currently, the molecular mechanisms of CIN progress remain poorly understood, and it is interesting to unravel this from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 36 publications
0
17
0
Order By: Relevance
“…Genome sequence analysis and bioinformatics prediction indicate that microRNA-466 is highly homologous with the LCR region prediction miRNA of HPVl6/18, while the LCR region is the regulatory region of carcinogenic key protein expression [ 30 ]. Lots of evidence has shown that high-risk type HPV (HPV16/18) infection is a prominent risk factor for cervical cancer development [ 31 ]. MiRNAs may act as a bio-marker in cervical cancer tissue or cervical lesions which are related to HPV16/18 infection [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Genome sequence analysis and bioinformatics prediction indicate that microRNA-466 is highly homologous with the LCR region prediction miRNA of HPVl6/18, while the LCR region is the regulatory region of carcinogenic key protein expression [ 30 ]. Lots of evidence has shown that high-risk type HPV (HPV16/18) infection is a prominent risk factor for cervical cancer development [ 31 ]. MiRNAs may act as a bio-marker in cervical cancer tissue or cervical lesions which are related to HPV16/18 infection [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…16 Lots of evidences have shown that high-risk type HPV infection is a high-risk factor for cervical cancer development. 17 MiRNAs may act as biomarkers in cervical cancer tissue or cervical lesions, which is related with HPV16/18 infection. 18,19 However, there is no study concentrating on the expression levels of miR-466 in cervical cancer.…”
Section: Discussionmentioning
confidence: 99%
“…CERNIA can be used to study the ceRNA competition among different tissue types, and different classes of genes. The ceRNAs prediction method is based on the DT-Hybrid recommendation algorithm [ 39 , 40 ].…”
Section: Methodsmentioning
confidence: 99%